2006
DOI: 10.1136/bjsm.2005.021980
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory observations in soccer match play: professional and recreational level applications using an intestinal pill system to measure core temperature

Abstract: Background: Technological limitations associated with oesophageal and rectal temperature probes have previously limited match play observations of body temperature. Objective: To investigate the application of an intestinal pill system to measure core temperature during dynamic, field based, soccer matches. Methods: Core temperature (T c ) was assessed using the intestinal pill system (CorTemp 2000) and changes in plasma volume were calculated using the values for haemoglobin and packed cell volume obtained be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 24 publications
5
43
1
5
Order By: Relevance
“…Two other studies have yielded similar findings. 15,20 Although the average initial core temperature in our investigation was 37.96C 6 0.46C compared with the rectal norm of 37.66C, 21 Gant et al 14 suggested that this might be explained, in part, by an absolute difference of 0.156C between advanced regions of the colon and rectum, and our participants were warmed up slightly because they had walked to the laboratory.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Two other studies have yielded similar findings. 15,20 Although the average initial core temperature in our investigation was 37.96C 6 0.46C compared with the rectal norm of 37.66C, 21 Gant et al 14 suggested that this might be explained, in part, by an absolute difference of 0.156C between advanced regions of the colon and rectum, and our participants were warmed up slightly because they had walked to the laboratory.…”
Section: Discussionmentioning
confidence: 87%
“…Further research is necessary to understand measurement of core temperature along the GI tract. 15 To our knowledge, no researchers have studied agreement of multiple sensor measurements at more than 11.5 hours after ingestion. Athletic events, such as twicedaily football practices and ultraendurance events, can last more than 12 hours.…”
mentioning
confidence: 99%
“…En deportes de equipo, como el fútbol, se ha visto que gran cantidad de deportistas llegan al inicio de la disputa deportiva en un estado de deshidratación y que pérdidas relevantes de peso por sudoración pueden ser un obstáculo en cuanto a la práctica deportiva se refiere 2 . Además se ha observado que durante los partidos de fútbol, las oportunidades para ingerir líquidos están reducidas por la falta de interrupciones en el juego 3 . Según el estudio de McGregor y Cols.…”
Section: Introductionunclassified
“…37 According to the results of an outdoor validity study conducted by our laboratory, 1 INT was a valid estimate of internal body temperature. Mean bias was higher outdoors (20.196C [20.346F]) 1 than indoors (20.026C [20.036F]), but these levels of bias are similar to those found in other studies 22,28 and are still considered valid.…”
Section: Intestinal Temperaturementioning
confidence: 99%